OF SOCIAL NETWORKS AND LINGUISTIC INFLUENCE: THE LANGUAGE OF ROBERT LOWTH AND HIS CORRESPONDENTS - Tieken-Boon van Ostade, Ingrid (International Journal of English Studies, 2009)
Analysing the unpublished correspondence of Robert Lowth, author of A Short Introduction to English Grammar (1762), this article attempts to find evidence of linguistic influence between people belonging to the same social network. Such evidence is used to try and determine where Lowth found the linguistic norm he presented in his grammar. Adding to the data presented by Nevalainen and Raumolin Bmnberg (2003) on the basis of their study of fourteen morphosyntactic items in the Corpus of Early English Correspondence, a detailed analysis is presented of eighteenth-century English. One of the results is an explanation for the presence in Lowth’s grammar of the stricture against double negation at a time when double negation was no longer in current use.